Disbursement of Credit Under the SGSY Scheme : A Comparison of SHGs’ Swarozgaris and Individual Swarozgaris - Arora, Manpreet; Singh, Swati (Indian Journal of Finance, 2016)
The development of the rural sector has always remained a priority for the government of a developing country. Growth of a country depends on the development of an individual. Therefore, in order to attain the goal of overall development, it becomes important for the government to concentrate on each and every sector of the economy. The rural sector of a developing country requires more attention than the urban sector as most of the population resides in rural areas. The government should make effective and productive steps for achieving the growth objective of the rural sector by initiating new policies and schemes. One of such initiatives taken by the government was the initiation of Swaranjayanti Gram Swarozgar Yojana (SGSY). Benefits of this scheme are received by the poor who can be divided into categories, that is, self help group (SHG) swarozgaris and individual swarozgaris. The purpose of the paper was to study whether the means between the two groups differ significantly or not. The study found significant difference between the means of credit disbursed to SHGs and individual swarozgaris.